Reexpressing terms in the novel “Bygone days” by Abdulla Qodiri - Tursunov, Elmurod (The Lingua Spectrum, 2025)
No matter how important the role of terms, which are considered the object of terminology examination, is in the development of the modern Uzbek literary language, in the 20th century Uzbek literary studies, terms have played a leading role in preserving the purity of the language, realizing new discoveries, concepts and trends that emerged as a result of socio-political changes, and enriching the vocabulary of the language. In tne novel “Bygone Days” by Abdullah Kadiri, one can also find many terms and terms related mainly to religion, architecture and construction, and other fields of science. An analysis of specialized literature on terminology shows that many opinions have been expressed by industry experts regarding the clarification of the terminology. This article reflects the difficulties and methods of overcoming them in translating terms into English in the novel “Bygone Days” by Abdulla Qodiriy, one of the representatives of the Uzbek Jadid movement, which is considered the crown jewel of Uzbek national novelism, to what extent the terms have found their equivalents in the English translations of the novel, and the problems of classifying terms. The article presents the translation methods used to solve the difficulties in translating terms into English using examples from all three translation options of the work using a comparative-analytical method.